SANITATION MANAGEMENT AT THE TECHNICAL SERVICES UNIT OF THE KAMBUNG FISH LANDING BASE, WEST SUMATRA PROVINCE - Andi Amir Muhammad Yusuf Mukhtar; Syaifuddin Syaifuddin; Nofrizal Nofrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
ABSTRACK The Kambang fish landing base in West Sumatra Province is one of the centers for capture fisheries activities, starting from filling supplies to fishing fleets. The formulation of the problem in this research is how to apply sanitation in the technical service of the Kambang Fishing Port (PPI) in West Sumatra Province and see how the supervision of the implementation of sanitation in the technical service of the Kambang Fish Base Port (PPI) in West Sumatra. The research was conducted using a survey method, namely direct observation of objects in the form of sanitation management in the PPI Kambang technical service to respondents by distributing questionnaires. This research procedure went through two stages which were carried out in a structured manner, namely the data collection stage and the data analysis stage. The data taken are interview and observation data, then the data is analyzed descriptively, from the analysis it is obtained that it shows that the implementation of sanitation at the PPI Kambang port of West Sumatra is quite good, it can be seen from the assessment of the condition of facilities and infrastructure which is at a value of 4.2 with good criteria.Keyword : Sanitation, Technical Service Unit, Fish Landing Base